2000
DOI: 10.3354/meps202001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photosynthetic carbon allocation in algal assemblages of Arctic sea ice with decreasing nutrient concentrations and irradiance

Abstract: Photosynthetic carbon assimilation into protein, low-molecular-weight metabolites (LMWM), polysaccharides, total lipids and into 3 lipid classes (neutral lipids, glycolipids and phospholipids) was determined in batch-culture experiments with natural assemblages of Arctic-ice algae under simulated in situ irradiance. Photosynthate allocation in 3 parallel batch incubations revealed a high contribution of lipid assimilation to total particulate carbon production (54.6 ± 0.4%) followed by LMWM (35.0 ± 1.0%), carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 81 publications
2
27
0
Order By: Relevance
“…Søreide et al 2006). Considering pretreatment of POM samples for estimating representative food web baseline values it may be appropriate to remove lipids, since algae also vary in their lipid content (Doucette & Fryxell 1985, Mock & Gradinger 2000. The increase in δ 15 N values after lipidremoval for Ice-POM was only slightly larger than the analytical precision level for δ 15 N values in this study, and should thus not lead to any ecologically significant implications for inferences of carbon sources.…”
Section: Comparability Among Studies In a Pan-arctic Perspectivementioning
confidence: 74%
See 2 more Smart Citations
“…Søreide et al 2006). Considering pretreatment of POM samples for estimating representative food web baseline values it may be appropriate to remove lipids, since algae also vary in their lipid content (Doucette & Fryxell 1985, Mock & Gradinger 2000. The increase in δ 15 N values after lipidremoval for Ice-POM was only slightly larger than the analytical precision level for δ 15 N values in this study, and should thus not lead to any ecologically significant implications for inferences of carbon sources.…”
Section: Comparability Among Studies In a Pan-arctic Perspectivementioning
confidence: 74%
“…Hobson et al 1995, 2002, Hop et al 2002, Tamelander et al 2006), but not always (Dunton et al 1989, Iken et al 2005. Algae also vary in their lipid content and particularly at the end of the growth season they may build up large lipid stores in response to nutrient stress (Fahl & Kattner 1993, Lindqvist & Lignell 1997, Mock & Gradinger 2000. However, lipid extraction of samples of particulate organic matter (POM) prior to stable isotope analysis has only been done in 2 recent Arctic marine food web studies (Søreide et al 2006, Tamelander et al 2006.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopic analyses of sea ice algae from Rijpfjorden revealed furthermore the occurrence of droplets that probably represent storage lipids in diatoms sampled in June, but not in April. Contrary to these field data, experimental studies by Mock & Gradinger (2000) showed no increase in storage lipids, but a dominance of glycolipids under decreasing nutri- Potential reasons for an increased allocation of photosynthetically fixed carbon to neutral (storage) lipids can be nutrient limitation (Lizotte & Sullivan 1992), increased irradiance (Smith et al 1989), or generally the transition to the stationary growth phase. In particular, a lack of silicate has been proven to increase the lipid content of diatoms substantially (Taguchi et al 1987).…”
Section: Changes In Fatty Acid Composition and Implications For Growtmentioning
confidence: 82%
“…Experimental studies addressing the role of nutrients and light in the lipid and fatty acid composition of ice algae revealed an increase in storage lipid production under N-limitation (Mock & Kroon 2002a), as well as a growing desaturation of chloroplast membrane lipids under light limitation (Mock & Kroon 2002b). Especially low-light acclimated sea ice algae react to nutrient depletion and decreasing irradiances by increasing glycolipid production (Mock & Gradinger 2000).…”
Section: Introductionmentioning
confidence: 99%